The confiscation in the Organic Integral Criminal Code - Rodríguez Tapia, Beatriz (2022)
The globalization process and the industrial revolution that the world is going through have led criminal organizations to perfect their production systems, generating millions of dollars in profits and becoming one of the greatest threats to both national States and the international community. Thus, since the seventies of the last century, several international instruments have been generated with the aim of providing legal tools and developing cooperation mechanisms to combat transnational organized crime, one of them is confiscation. In the Ecuadorian legal system, this figure is present since its first criminal normative bodies; however, it is not until the issuance of the Organic Integral Criminal Code in 2014, where recommendations of several international instruments of particular relevance are collected, constituting today as one of the main weapons of the Ecuadorian State to combat organized crime.